Pembelajaran kooperatif dalam pendidikan jasmani: Tinjauan sistematis di Indonesia - Gazali, Novri; Setiawan, Edi; Abdullah, Khairul Hafezad; Rusmanto; Sulastio, Agus; Nazirun, Novia (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
The purpose of this literature review is to review the scientific literature on cooperative learning research in physical education in Indonesia. Two databases (Scopus and Web of Science) were used to select articles containing information on cooperative learning in physical education. The search was conducted following the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. After the exclusion criteria, only 7 articles were included in the category. The results show that the types of research used in cooperative learning research in Indonesia vary, namely; quantitative, mixed research (quantitative and qualitative), and development. On average in the study using questionnaires and interviews in data collection. Cooperative learning research in Indonesia is also divided into three groups, (i) cooperative learning models based on local wisdom and basic skills cards (FS), (ii) cooperative learning models of TGT, STAD, and Jigsaw types in sports and online learning, (iii) cooperative learning model in instilling self-confidence, cooperation and moral values. Several limitations inherent in the review have been noted, and it is necessary to carry out further studies of this globally with literature reviews or mapping studies (bibliometric and scientometric), and it is also necessary to do about the application of cooperative learning and its impact, because in today's society, elements of elements such as social relationships, dialogue, and respect, as well as physical activity and sport, are very important.